(−) and (+)-Merrilliaquinone, a pair of new quinone enantiomers from Illicium merrillianum and their distinctive effect on human hepatoma and hepatic cells. Issue 93 (11th October 2015) - Tian, Xinhui; Li, Li; Pei, Jinpeng; Yue, Rongcai; Fang, Xin; Zhang, Jianping; He, Weiwei; Shan, Lei; Shen, Yunheng; Zhang, Weidong
<x xml:space="preserve">Abstract</x> Two new quinone enantiomers (−) and (+)-merrilliaquinone (1a, 1b) were isolated from Illicium merrillianum, 1b exhibited a selective cytotoxicity between human hepatoma cell lines and normal human hepatic cells, while 1a didn't have such activity.